The Psychology of Resistance: Why Our Minds Avoid Work and How to overcome it - N. V. Sowmya,; J. P. Pramod, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Resistance to work is a predominant behavioral challenge modulated by mental strain, fatigue, fear of failure, perfectionism and burnout. The key factors include low interest, burnout or exhaustion, procrastination and resistance to change or reluctance towards new experiences that often cause individuals to avoid their tasks. However, the brain’s constant need for immediate rewards over long-term gains also solidify this resistance. This article identifies the intrinsic factors of work resistance, validated by data illustrations and cognitive theories, and provides feasible solutions such as thought reframing, behavioral conditioning, systematic work methods and cognitive management techniques. By discerning these cognitive constraints, individuals can enhance an effective, resilient and practical approach to work, eventually formulating operational capacity and overall quality of life.
Keywords: Cognitive overload; Decision fatigue; Dopamine; Mental fatigue; Motivation; Procrastination; Self-regulation